LIKE CATCHING A WAVE: QUALITATIVE STUDY OF EEG NEUROFEEDBACK GAME CONTROLS - Kaplan, Cyril (PEOPLE: International Journal of Social Sciences, 2018)
Seven musicians engaged in EEG neurofeedback (NF) training of a new protocol designed to practice the switch between different mindsets. Three different sonic games programmed to reward distinct EEG parameters were administered twice in a row. Interviews were performed after each training session in order to obtain full description of the inner processes that surfaced while playing the NF game. The interviews were subjected to theoretically driven thematic analysis (Braun & Clarke, 2006) to identify the ways of direct interaction of the player with the NF game, through the optics of the player.We were able to identify 22 different techniques that were used to control the game, further referred to as neurofeedback game controls, which can be loosely united under six superordinate terms: body movements, different levels of activation, direction of attention, interaction with the sound, thoughts that change the mindset, the flow.Most of the individual game controls have a different function in each of the three different games of our training protocol, the effectivity of each one varying between players. Nevertheless, several game controls appeared to have power over all three games and across the subjects – a mindset characterized by thoughts scoping through the player’s focus unwillingly while attracting her attention was leading to a failure in the NF game, while a mindset characterized by the absence of content attracting attention was associated with the success in the NF game. Delving deeply into the game, concentrating without trying hard and closing the eyes also helped the players to better perform in all three games. Furthermore, the feeling of being successful in the game led to further success.This paper aims to explore an insufficiently described area of NF research and possibly offer an alternative framework that, in the future, when more knowledge is accumulated, would provide neurofeedback researchers and practitioners with more vocabulary theoretically useful for further research and practice.